Diversification of Processed Moringa into Chips in the Community of Balombong Village, West Sulawesi Province - Phika ainnadya hasan; Firdaus Firdaus; Mufti Hatur Rahmah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Moringa is a plant that is easy to find in Balombong Village. All people's houses have moringa as a garden plant. People use moringa limited to vegetables. This activity aims to provide training to the people of Balombong Village in processing Moringa into chips. This community service activity uses the community development method with a training approach. Participants showed enthusiasm during the activity. Questionnaire analysis showed that 95.1% of the public knew that moringa could be processed into chips. But all (100%) people have never made chips from moringa. Therefore all people think that this activity is very useful.